2011
DOI: 10.1002/bse.710
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Ecopreneurs' Decisions to Sell Up

Abstract: This article examines the phenomenon of values-based firms being sold to larger mainstream firms. Its focus is on the sensemaking rationale offered by a New Zealand ecopreneur who sold an organic beverage company after twenty years at the helm. The company case study is presented through two enterprise development narratives based on alternative sensemaking modes. Key values-related challenges arising in ecopreneurial business are identified including: 1) adhering to the founder"s values; 2) growing the busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 30 publications
(30 reference statements)
2
54
0
1
Order By: Relevance
“…Alternative producers sometimes justify this by arguing that large-scale, industrialized methods are the fastest way to "scale up" alternative farming practices so that they can compete in supply chains with conventionally managed systems (Box 4). In search of new markets, many dominant food corporations have purchased and integrated successful organic producers and alternative food companies into their product portfolios (Kearins and Collins 2012). This trend of purchasing "sustainable" product businesses is also observed in other sectors, such as personal care, paper, and cleaning chemicals.…”
Section: Alternative Agri-food Network Food Sovereignty and Justicementioning
confidence: 99%
“…Alternative producers sometimes justify this by arguing that large-scale, industrialized methods are the fastest way to "scale up" alternative farming practices so that they can compete in supply chains with conventionally managed systems (Box 4). In search of new markets, many dominant food corporations have purchased and integrated successful organic producers and alternative food companies into their product portfolios (Kearins and Collins 2012). This trend of purchasing "sustainable" product businesses is also observed in other sectors, such as personal care, paper, and cleaning chemicals.…”
Section: Alternative Agri-food Network Food Sovereignty and Justicementioning
confidence: 99%
“…These include companies considered as international models of sustainability such as Patagonia, Body Shop, and Interface (Kearins and Collins 2012;Fowler and Hope 2007;Stubbs and Cocklin 2008). Whatever the organization's size and environmental commitment, the top managers' leadership clearly plays a key role in corporate greening (Kearins and Collins 2012;Egri and Herman 2000).…”
Section: Environmental Leadership and Corporate Greeningmentioning
confidence: 99%
“…The successful implementation of environmental practices (i.e., the implementation of a sustainability policy, pollution prevention actions, promotion of industrial ecology, training programs, etc.) presupposes an active commitment from top managers (Kearins and Collins 2012;Revell and Blackburn 2007;Revell et al 2010). Second, studies on the motivations behind environmental leadership and corporate greening have shown the importance of the search for social legitimacy and response to stakeholder expectations.…”
Section: Environmental Leadership and Corporate Greeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research has for the most part focused on the socially oriented enterprises that have been acquired by MNCs, addressing questions such as whether the enterprise has changed following the acquisition and why the founders of those enterprises chose to sell their businesses (e.g. Austin and Leonard 2008;Kearins and Collins 2012;Nazarkina 2012). There has been very little direct research on the choices and motives of the MNCs driving the acquisition, and how they manage the post-acquisition integration process.…”
Section: Introductionmentioning
confidence: 99%